Pest categorisation of Thecaphora solani - Bragard, Claude (John Wiley and Sons Inc., 2018)

(untitled) (EFSA J)
The Panel on Plant Health performed a pest categorisation of the fungus Thecaphora solani, the causal agent of smut of potato, for the EU. The identity of the pest is well established and reliable methods exist for its detection and identification. T. solani is present in Bolivia, Chile, Colombia, Ecuador, Mexico, Panama, Peru and Venezuela. The pathogen is not known to occur in the EU and is listed in Annex IAI of Directive 2000/29/EC, meaning its introduction into the EU is prohibited. The major host is Solanum tuberosum (potato), but various other tuber‐forming Solanum species are also affected. The pest has also been reported on Solanum lycopersicum (tomato), and wild solanaceous plants are also affected. All the major hosts and pathways of entry are currently regulated. Host availability and climate matching suggest that T. solani could establish in parts of the EU and further spread by human‐assisted means. The disease induces gall formation on potato tubers, stolons and underground stem parts, reducing yield and making tubers unmarketable. The pest introduction in the EU would potentially cause impacts to potato production. In the infested areas, the only available strategy to control the disease and prevent it from spreading is the application of quarantine and sanitation measures and the cultivation of resistant varieties. The main uncertainties concern the host range, the biology and epidemiology of the pest, and the potential of the pest to enter the EU through three unregulated minor pathways. T. solani meets all the criteria assessed by EFSA for consideration as potential Union quarantine pest. The criteria for considering T. solani as a potential Union regulated non‐quarantine pest are not met, since the pest is not known to occur in the EU.